Dermoscopy improves diagnostic accuracy for clinically amelanotic nodules. (19th August 2018) - Lin, Matthew J; Xie, Charles; Pan, Yan; Jalilian, Chris; Kelly, John W
Abstract: Background/Objectives: Amelanotic nodular melanomas are notoriously difficult to diagnose and are responsible for a disproportionate burden of melanoma mortality. It is important to distinguish them from other amelanotic nodules. This study aimed to describe the dermoscopic features of a series of nodular melanomas and other amelanotic nodules and to determine whether dermoscopy improves diagnostic accuracy. Method: Retrospective analysis of 150 clinically amelanotic nodules with macroscopic and dermoscopic images. Results: In terms of classifying the nodules as malignant, dermoscopy was superior to unaided eye (specificity 89%; 95% CI 71–98% vs 67%; 95% CI 46–83%, P = 0.03). Dermoscopy enhanced sensitivity for the diagnosis of both amelanotic melanoma and SCC. In 19% of cases, using dermoscopy, the most likely diagnosis was changed from incorrect to correct. This included 26% of amelanotic melanomas which had a macroscopic misdiagnosis overturned to the correct diagnosis. Polymorphous vascular structures were more common in malignant nodules. 76% of amelanotic melanomas/Merkel cell carcinomas had polymorphous vessels compared with 38% of SCCs/KAs/BCCs and 22% of benign nodules ( P < 0.001). Conclusion: Dermoscopy improves diagnostic accuracy for amelanotic melanomas and other amelanotic nodules. Although dermoscopy improves diagnostic accuracy for amelanotic melanomas, these aggressive melanomas remain diagnostically difficult.